RECORD OF THE BLURRED SMOOTH LANTERNSHARK, Etmopterus bigelowi SHIRAI and TACHIKAWA 1993 (SQUALIFORMES, DALATIIDAE), IN SOUTHERN BRAZILIAN WATERS - Canani , Gabriel; Oddone, Maria Cristina (Boletín de la Sociedad Zoológica del Uruguay, 2020)
In this paper the occurrence of an immature female specimen of the Blurred Smooth Lanternshark, Etmopterus bigelowi is recorded. The individual was caught by a longline vessel using a bottom hook on March 20th, 2014, off South Brazil.